Uji Molecular Docking Annomuricin E dan Muricapentocin pada Aktivitas Antiproliferas - ROSA ADELINA (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Various natural compounds have been reported to be used as anticancer, however their modes of action have not been clearly defined. One of the plant compounds is acetogenin which can induce apoptosis in in vitro study. Two new acetogenins discovered in Annona muricata are annomuricin E and muricapentocin. Molecular docking is one of in silico model to screen coumponds based on their mechanism to protein. Therefore, the two compounds were docked using PLANTS 1.1 to see the affinity to proliferation protein, Protein Kinase C. The RMSD calculations of the best predicting binding site gave 1.3906 Å. The molecular docking results of native ligand (07u), annomuricin E, and muricapentocin are -71.161; -127.739; and -116.868. It showed that annomuricin E has the best in silico affinity to Protein Kinase C, and has better ability to inhibit proliferation as compared to the native ligand and muricapentocin.